A comprehensive study on haematological and platelet related changes following septoplasty - Senniappan, Shivakumar; Giritharan, Naveen (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Septoplasty is an elective surgical procedure indicated for the improvement of anatomic nasal airway obstruction. Platelets have an important role in endothelium damage repair and regulating hemostasis. Platelets produce pro-inflammatory mediators such as cytokines and chemokines during vascular inflammation. Aim of the study was to determine various types of changes that occur in Haematology and Platelet profile in patients after they undergo Septoplasty. Methods: The study was conducted between January 2019 to June 2020 on 50 patients attending ENT OPD in Vinayaka Mission’s KirupanandhaVariyar Medical College and Hospital, Salem. 50 patients fulfilling inclusion/ exclusion criteria who give informed consent were included in the study. Results: The parameters with no significant differences were found in red blood cells, white blood cells, platelet count, erythrocyte sedimentation rate, haemoglobin (Hb), hematocrit (Htc), mean corpuscular volume, mean corpuscular hemoglobin concentration (MCHC), and platelet distribution width values. mean platelet volume (MPV) value was decreased, platelet-to-lymphocyte ratio (PLR) and neutrophil to lymphocyte ratio (NLR) values were increased. Conclusions: In our study, MPV value was decreased, PLR and NLR values were increased significantly after septoplasty. Also, the decrease in nasal obstruction symptom evaluation (NOSE) score after surgery is the confirmatory parameter proving that septoplasty not only improves the quality of life but also significantly corrects the altered blood and platelet related parameters in nasal septal deviation patients.